2015
DOI: 10.12928/telkomnika.v13i4.1827
|View full text |Cite
|
Sign up to set email alerts
|

Distinguish Sea Turtle and Fish Using Sound Technique in Designing Acoustic Deterrent Device

Abstract: Acoustic is a common method for underwater object classification and to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In order to cover maximum length of the pipeline with low energy and more network life time, we have defined the different ranges of acoustic communication for each types of sensor varying from 200 meter to more than 1000 meter. It is found that acoustic communications work best for the short range applications because it support bandwidth of 20-30 KHz [22][23][24] in 1 km distance. Although, in special cases, we can increase this range of sensors [25], but in normal acoustic communication it is suggested to use the discussed ranges of sensors.…”
Section: Related Workmentioning
confidence: 99%
“…In order to cover maximum length of the pipeline with low energy and more network life time, we have defined the different ranges of acoustic communication for each types of sensor varying from 200 meter to more than 1000 meter. It is found that acoustic communications work best for the short range applications because it support bandwidth of 20-30 KHz [22][23][24] in 1 km distance. Although, in special cases, we can increase this range of sensors [25], but in normal acoustic communication it is suggested to use the discussed ranges of sensors.…”
Section: Related Workmentioning
confidence: 99%
“…Target strength is the acoustic size of a target in form of decibels (dB). The TS measurement suggested using echo signal observation from the transducer output [13].…”
Section: Echo Voltage and Target Strengthmentioning
confidence: 99%